Is climate a risk multiplier in the Central American Dry Corridor? A CGIAR study - Pacillo, Grazia; Achicanoy Estrella, Harold Armando; Ramírez Villegas, Julián Armando; Craparo, Alessandro Carmelo William; Basel, Ashleigh Megan; Villa, Victor; Liebig, Theresa Ines; Schapendonk, Frans; Carneiro, Bia; Resce, Giuliano; Ruscica, Giosuè; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2021)
In this study, we investigate the climate-food security-conflict nexus in the Central American dry corridor as part of the WFP - CGIAR project "Assessing the relationship between climate, food security and conflict in Ethiopia and in the Central American Dry Corridor (CADC). Quantitative analysis on the impact of climate variability on conflict in Ethiopia and in the CADC countries". Our main findings can be summarized as follows: (1) Climate exacerbates foodinsecurity, poverty and inequalitythat can lead to more frequent conflicts. (2) The impact of climate on foodinsecurity can cascade inmultiple, wider security risks (3) There exist “climate insecurityhotspots” at sub-national levelwhere high level of climatevariability, conflict intensity anddiversity co-occur with otherexisting socio-economicinsecurities.